Clustering approach to protein folding problem and dynamics of the tropical atmosphere - Mikhail Filippov (2016)
Many different multidimensional and multivariate data-sets are studied currently in almost all research areas. Usually, the aim of such studies is to reveal meaningful patterns and to gain an insights about special characteristics of the particular data-set. It is usually done by scanning over the elements of the data-set at large and bringing up groups or clusters of these elements that exhibit correlations across the variables or dimensions. In this thesis I use different techniques to address two problems: protein folding and the dynamics of the tropical atmosphere.